Normative prosthodontic care need: does it impact the daily life of young Saudis with high level of oral diseases? A cross sectional study - Fahad Al-Harbi; Maha El Tantawi (BMC, 2017)
Abstract Background Assessing the need for prosthodontic care previously included older age groups. There is less information about younger populations who may need this care because of high disease levels. The aim of this study was to assess the normative need for prosthodontic care in a young Saudi population with high oral disease levels, the associated factors and its impact on daily life. Methods A cross sectional study included Saudi adults in the Eastern Province in 2016. A questionnaire was used to assess personal background (confounders), risk factors affecting oral diseases (exposures) and the impact of oral problems on daily life. A clinical examination assessed tooth loss, the presence of prosthodontic appliances, the presence of untreated decay and need for periodontal care. Directed acyclic graphs identified the confounders to be included in regression models with separate outcomes: normative need for prosthodontic care (binary logistic model) and impact on 6 daily life aspects (ordinal regression models). Results Complete data were available for 574/ 700 = 82% and 46.7% needed prosthodontic care with 2 lost teeth on average among adults of mean age = 33.2 years. The confounders controlled for the need for prosthodontic care included socioeconomic status (SES), dental visits last year and health insurance. The confounders for the impact on daily life included age and SES. In adjusted models, normative need for prosthodontic care was significantly associated with untreated decay (OR = 2.09, 95% C.I. = 1.37, 3.19). The impact on daily life was not significantly associated with prosthodontic care need but with untreated decay, especially sleeplessness (regression coefficient = 0.53, 95% C.I. = 0.02, 1.04) and dropping daily activities (regression coefficient = 0.79, 95% C.I. = 0.13, 1.46). In addition, the need for periodontal care was associated with food avoidance (regression coefficient = 0.73, 95% C.I. = 0.28, 1.18). Conclusions In Saudi adults in the Eastern Province, there was a considerable normative need for prosthodontic care due to untreated decay. The impact on daily life was related to the underlying oral diseases rather than the need for prosthodontic care itself.